Ophthalmia Secondary to Cobra Venom Spitting in the Volta Region, Ghana: A Case Report - Lanzetta, Maria Andrea (Case Rep Ophthalmol, 2017)
PURPOSE: To report the first case of ophthalmia due to contact with cobra venom in the Volta Region, Ghana. METHODS: An ointment containing vitamin A was applied to treat the patient's unilateral defects in the corneal epithelium and the consequent diminished visual acuity. RESULTS: Healing of the corneal epithelium and improvement of visual acuity were observed after only 1 day. CONCLUSIONS: This case suggests that consequences of cases of cobra venom spitting in the eyes can be minimal if immediate treatment is provided.